Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

Les conditions favorables à l’établissement de services de santé pour les aînés francophones - Forgues, Éric; Couturier, Yves; Deroche, Francine (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire - MacLean, Patsy; Robinson, Constance; Lewis, Kay; HRA, firme d’experts-conseils (Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français, 2007)

Soins de longue durée en français. Rapport final - McQuaid, Steve (The Atlantic Evaluation Group Inc, 2010)

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Améliorer l’accès des personnes âgées du Manitoba et de l’Île-du-Prince-Édouard aux services de santé en français - Société Santé en français (2014)

Agir ensemble pour une Petite enfance en santé dans les communautés francophones et acadienne en situation minoritaire : Résultats et impacts du programme Petite enfance en santé 2024-2025 - Société Santé en français et les Réseaux de santé en français (2025)